This preview shows page 1. Sign up to view the full content.
Unformatted text preview: V-( z,t = 0 + ) = 1 / 3 V and V + ( z,t = 0 + ) changes to V + ( z,t = 0 + ) = V-( z,t = 0 + ) S = 1 / 3(-1) =-1 / 3 V leaving zero volts on the line. Once this wave reaches the load, V-( z,t = /v + ) changes to V-( z,t = /v + ) = V + ( z,t = /v + ) L =-1 / 3(1 / 2) =-1 / 6 V putting-1 / 2 volt on the line. When this wave gets back to the source end, the new V + value is +1/2 V again canceling the voltage on the line. [The extra page provided 09/11/18.] CORNELL UNIVERSITY c WES SWARTZ (09/8/14) 102...
View Full Document